WHAT ARE THE SOCIO-DEMOGRAPHIC FACTORS INFLUENCING MALE INVOLVEMENT IN ANTENATAL CARE AMONG CLIENTS ATTENDING ANTENATAL CLINIC AT NEBBI GENERAL HOSPITAL, NEBBI DISTRICT? - Adero , Teddy; ATIM , MIRIA; Awoi , Ronald (SJ Insights, 2024)
Background Antenatal care (ANC) is crucial for maternal and fetal health, yet male involvement in ANC remains low globally. Despite efforts to encourage male participation, studies indicate low levels of involvement across Africa, including Uganda. This study aims to identify factors influencing male involvement in ANC at Nebbi General Hospital. Methods The study employed a cross-sectional quantitative approach using purposive sampling to collect data from pregnant women and their partners attending the antenatal clinic, with a final sample size of 37 participants, and data analysis conducted using SPSS version 20.0 Results A 100% response rate with 37 participants, revealed education level, number of children, alcohol consumption, and satisfaction with services, as key determinants of male involvement. Conclusion Various socio-demographic factors significantly influence male participation in antenatal care (ANC), affecting maternal and child health outcomes. Recommendation To improve male involvement in ANC, the Ministry of Health should implement educational programs targeting men, especially those with lower education. Nursing implications Nurses should educate expectant mothers and their male partners on the importance of male involvement in ANC and its impact on pregnancy outcomes, advocating for flexible clinic hours.